Post-World War II Brazil: A New Homeland for Jews and Nazis? - Valente, Sarah R. (Comparative Cultural Studies - European and Latin American Perspectives, 2021)
There is a dearth of research on Holocaust survivors who immigrated to Brazil before, during, and after World War II. Also missing is a comprehensive analysis of how former Nazis escaped to the country after the War. This “co-existence” of Jewish survivors and Nazis within the same geographical location at the same time is a topic of great complexity, which I explore in this paper. In the first section of this paper, I will briefly address Brazil’s political history, while at the same time, its identity as an immigrant country, with a historically multi-ethnic cultural and demographic make-up, by analyzing the census data available. To explore how Jews negotiated their new position as survivors, immigrants, and members of a minority group who, while lived with the possibility of coexisting with war criminals, in section two, I analyze the memoirs of Aleksander Laks and Sabina Kustin, who, in different ways, transferred their fears from the old world to their new realities, due to imagined or real Nazi presence, which afflicted their existence and identity as Jews in Brazil. In the last section, I address the question of Nazi presence in Brazil. Using newspaper articles and governmental documentation, I highlight strategies used by war criminals such as Herbert Cukurs and Gustav Franz Wagner, to live freely in Brazil, and evade justice.